Trade Costs, Export Development and Poverty in Rwanda - Diop, Ndiame; Brenton, Paul; Asarkaya, Yakup (World Bank, Washington, DC, 2012)
For Rwanda, one of the poorest countries in the world, trade offers the most effective route for substantial poverty reduction. But the poor in Rwanda, most of whom are subsistence farmers in rural areas, are currently disconnected from markets and commercial activities by extremely high transport costs and by severe constraints on their ability to shift out of subsistence farming. The constraints include lack of access to credit and lack of access to information on the skills and techniques required to produce commercial crops. The paper is based on information from the household survey and a recent diagnostic study of constraints to trade in Rwanda. It provides a number of indicative simulations that show the potential for substantial reductions in poverty from initiatives that reduce trade costs, enhance the quality of exportable goods, and facilitate movement out of subsistence into commercial activities.